2022
DOI: 10.1186/s13595-022-01155-7
|View full text |Cite
|
Sign up to set email alerts
|

Tree stumps — an important but undervalued dead wood pool

Abstract: Key message Dead wood in forests is an important resource due to its role for nutrient cycles, carbon budgets, and biodiversity, among other. While standing and downed dead wood are typically monitored in National Forest Inventories (NFI), stumps have not received comparable attention. Based on the detailed stump inventory in the current Swiss NFI, this study demonstrates the important contribution of stumps to the dead wood pool. Context Dead woo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
(61 reference statements)
0
4
0
Order By: Relevance
“…Due to its significant quantity and slow turnover, CWD plays a crucial role in nutrient release and long-term forest productivity, as well as maintaining ecosystem integrity and ecological processes [1,2]. Previous studies on CWD have mainly focused on standing dead trees, fallen logs, and large branches, primarily in natural forests or forests at higher latitudes or altitudes [3][4][5][6]. In intensively managed plantations, the main type of CWD is often stump-root systems left after logging [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Due to its significant quantity and slow turnover, CWD plays a crucial role in nutrient release and long-term forest productivity, as well as maintaining ecosystem integrity and ecological processes [1,2]. Previous studies on CWD have mainly focused on standing dead trees, fallen logs, and large branches, primarily in natural forests or forests at higher latitudes or altitudes [3][4][5][6]. In intensively managed plantations, the main type of CWD is often stump-root systems left after logging [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Debeljak et al found that the underground biomass in Slovenian plantations ranged from 40.0 t/hm 2 to 48.2 t/hm 2 , while natural forests only had 2.0 t/hm 2 to 22.8 t/hm 2 [11]. Typically, the aboveground biomass of stump-root systems only represents a small portion of the total CWD biomass of plantation ecosystems, with the coarse roots being the main component [3]. However, excavating the underground part is labor-intensive, time-consuming, and costly [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations